Inspiratory muscle fatigue at the swimming tumble turns: its occurrence and effects on kinematic parameters of the turns - Moravec, Tadeja; Lomax, Mitch; Ušaj, Anton; Kapus, Jernej (Frontiers in Physiology, 2023)
The present study had two objectives: 1) to investigate the effects of tumble turns on the development of inspiratory muscle fatigue (IMF) and compare this to whole swimming, and 2) to evaluate the effects of pre-induced IMF on the kinematic parameters of tumble turns. Fourteen young club-level swimmers (13 ± 2 years of ages) completed three swim trials. The first trial was used to determine the 400-m front crawl swim time at maximal effort (400FC). The other two trials consisted of a series of 15 tumble turns at the 400FC pace. In one of the turn-only trials, IMF was pre-induced (TURNS-IMF), whereas in the other turn-only trial it was not (TURNS-C). Compared with baseline values, the values for maximal inspiratory mouth pressure (PImax) at the end of the swim were significantly lower at all trials. However, the magnitude of inspiratory muscle fatigue was less after TURNS-C (PImax decreased by 12%) than after 400FC (PImax decreased by 28%). The tumble turns were slower during 400FC than during TURNS-C and TURNS-IMF. In addition, compared to TURNS-C, turns in the TURNS-IMF were performed with higher rotation times and shorter apnea and swim-out times. The results of the present study suggest that tumble turns put a strain on the inspiratory muscles and directly contribute to the IMF observed during 400FC swimming. Furthermore, pre-induced IMF resulted in significantly shorter apneas and slower rotations during tumble turns. IMF therefore has the potential to negatively affect overall swimming performance, and strategies should be sought to reduce its effects.